(untitled) (International Journal of Management, Policy and Administrative Studies (IJMPAS), 2026)
The creation of Anioma State has been a topic of great interest in the political economy of South East Nigeria, especially among the Igbo Community in Delta state and Igbo tribe generally. This proposed state aims to address the long-standing marginalization of the Anioma people of Delta State and Ndigbo tribe and provide them with more political representation and resources. With the growing tension and political unrest in the region, the debate surrounding Anioma State creation has intensified. Proponents argued that it will bring about economic growth and development, while opponents raise concerns about its feasibility and potentials conflict with neighboring states. This paper delves into the historical, political landscape, and potential impact of Anioma State creation on Ndigbo South East Nigeria. It examines the various perspective and arguments surrounding the issue and provides insight into its potentials outcomes. The paper is qualitative one and utilized Political Economy theory and through a thorough textual analysis of literature, it aims to contribute to the ongoing discourse on the political economy of Anioma state creation and its implications on Ndigbo South East Nigeria. The paper strong recommends actual creation of the Anioma state to make up six Igbo states.